The Isoflavone Intake for Preventing Osteoporosis in Menopausal Women: A Review - Fariha Hinisa; Satra Yunola; Elvina Indah Syafriani (Faculty of Medicine, Universitas Negeri Surabaya, 2025)
Osteoporosis is a condition marked by reduced bone mass and structural deterioration, increasing the risk of fractures. Isoflavones have been proposed as an alternative treatment to manage osteoporosis-related symptoms. This study aimed to evaluate the effectiveness of the isoflavones in improving bone health. A systematic search was conducted using PubMed, ScienceDirect, and Google Scholar, following PRISMA 2023 guidelines to identify relevant studies. Articles were selected based on their investigation of isoflavones' effects on osteoporosis. A meta-analysis using a random-effects model was performed, with outcomes reported as odds ratios and 95% confidence intervals (CI). Two studies (total participants = 251) met the inclusion criteria. The findings indicated that isoflavones had a positive effect on increasing bone mineral density (BMD) in postmenopausal women with osteoporosis, showing a mean difference of 0.87 (95% CI: 0.42 to 1.78; p = 0.78). However, the improvement was not statistically significant compared to the placebo group. In conclusion, while isoflavones appear to support BMD, they did not show a significant advantage over placebo. Nonetheless, they may still be considered a potential complementary therapy for managing osteoporosis symptoms, especially in postmenopausal women.